The Pediatric Sleep Clinical Global Impressions Scale—A New Tool to Measure Pediatric Insomnia in Autism Spectrum Disorders. Issue 5 (June 2016) - Malow, Beth A.; Connolly, Heidi V.; Weiss, Shelly K.; Halbower, Ann; Goldman, Suzanne; Hyman, Susan L.; Katz, Terry; Madduri, Niru; Shui, Amy; Macklin, Eric; Reynolds, Ann M.
Abstract: Objective: To pilot a clinician-based outcome measure that provides complementary information to objective measures and parent-based questionnaires for insomnia in children with autism spectrum disorders (ASD). Method: The authors developed a Pediatric Sleep Clinical Global Impressions Scale (CGI). Questions included (1) the child's ability to fall asleep and remain sleeping independently (i.e., apart from parents); (2) bedtime resistance; (3) sleep onset delay; (4) night awakening; (5) parental satisfaction with their child's current sleep patterns; (6) family functioning as affected by their child's current sleep patterns; and (7) clinician's overall concern with the child's sleep. After refining the instrument through the evaluation of vignettes by ASD and sleep experts, the authors piloted the Pediatric Sleep CGI in a 12-week randomized trial of iron supplementation in children with ASD. Clinicians completed Pediatric Sleep CGIs and structured sleep histories, parents completed the Children's Sleep Habits Questionnaire (CSHQ), and children wore actigraphy watches. Results: In repeated measures models, the Pediatric Sleep CGI and CSHQ were correlated for sleep onset delay ( r = .66, p < .001), night wakings ( r = .40, p < .001), and total score ( r = .29, p < .001). The CGI-S sleep onset delay and actigraphy sleep onset delay scores ( r = .75, p = .0095) were also correlated. The overall CGI-S showed improvement with therapy ( p = .047). Conclusion: The Pediatric Sleep CGI shows promise in measuring clinician-rated outcomes in pediatric insomnia in children with ASD. Larger samples will be necessary to examine reliability, validity, and measure to change, as well as applicability to other populations with pediatric insomnia. Abstract : This article has supplementary material on the website: www.jdbp.org.